Presentations in medical education - Bandaranayake, Raja C.
"Drawing on over 43 years of experience, this book compiles the author’s extensive work on a variety of themes in medical education. Each chapter begins with an introduction to the subject, followed by more in-depth discussion of the topic. The book is replete with anecdotes and the personal experiences of the author, together with the lessons learnt from them. It will be of value to all those who are concerned with the education of health professionals, particularly trainers and trainees in degree and non-degree courses in Medical Education. Many of the chapters provide guidance to those entrusted with the noble task of training tomorrow’s health professionals."